2020
DOI: 10.1101/2020.05.04.076885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin Regulates Bipartite-Classified Small RNA Expression to Maintain Epigenome Homeostasis in Arabidopsis

Abstract: Eukaryotic genomes are partitioned into euchromatic and heterochromatic domains to regulate gene expression and other fundamental cellular processes. However, chromatin is dynamic during growth and development, and must be properly re-established after its decondensation. Small interfering RNAs (siRNAs) promote heterochromatin formation in eukaryotes, but little is known about how chromatin regulates siRNA transcription. We demonstrated that thousands of transposable elements (TEs) produce exceptionally high l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 112 publications
(157 reference statements)
0
4
0
Order By: Relevance
“…2 b), suggesting that euchromatic embryo hypermethylation might be common among plants. Recent work demonstrates that Arabidopsis heterochromatin is decondensed and produces abundant 24-nt siRNAs during embryogenesis [ 43 ], providing an opportunity for the RdDM machinery to access this chromatin for hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…2 b), suggesting that euchromatic embryo hypermethylation might be common among plants. Recent work demonstrates that Arabidopsis heterochromatin is decondensed and produces abundant 24-nt siRNAs during embryogenesis [ 43 ], providing an opportunity for the RdDM machinery to access this chromatin for hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…In B. rapa, we detect hypermethylation in both heterochromatin and euchromatin ( Figure 2B), suggesting that euchromatic embryo hypermethylation might be common among plants. Recent work demonstrates that Arabidopsis heterochromatin is decondensed and produces abundant 24-nt siRNAs during embryogenesis [42], providing an opportunity for the RdDM machinery to access this chromatin for hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that such abundance is associated with epigenetic safeguard mechanisms for controlling the expression of transposons and heterochromatic repeats during embryo development [16,20]. A recent study [21] showed that siRNAs generated from transposable elements (TEs), highly numerous in Arabidopsis embryos and typically 24-nt long, originate both from euchromatic TEs, being required not only during embryogenesis as a way of silencing TEs, but also from heterochromatic TEs specifically required during embryogenesis to help establish TE methylation de novo, which is then maintained during post-embryogenesis independently of siRNAs.…”
Section: Small Rna Expression Profiles In Embryonic Tissuesmentioning
confidence: 99%
“…Such as for the Arabidopsis model system, most frequently used for better understanding the regulation of SE, many differentially expressed miRNAs have also been identified in other embryogenic cultures of different gymnosperms [18], mono-and dicotyledonous plants [15,21,26,27]. From these studies, a large number of miRNAs has been associated with SE target genes related to auxin perception, signaling and biosynthesis, as presented in Figure 1.…”
Section: Auxins and Mirna-arf Interactionsmentioning
confidence: 99%